Advantaging Aggressors: Justice & Deterrence in International Law - Haque, Adil Ahmad (2011)
Current international law imposes limitations on the use of force to defend against unlawful aggression that improperly advantage unlawful aggressors and disadvantage their victims. The Article gives examples of such rules, governing a variety of situations, showing how clearly unjust they can be. No domestic criminal law system would tolerate their use. There are good practical reasons why international law should care that its rules are perceived as unjust. Given the lack of an effective international law enforcement mechanism, compliance depends to a large degree upon the moral authority with which international law speaks. Compliance is less likely when its rules are perceived as obviously unjust. This common sense perspective is supported by social science research showing the importance of law's moral credibility in gaining assistance and compliance, in reducing resistance and subversion, and in helping to shape shared norms. The current practice of victim states ignoring legal limitations, with studied indifference to such violations by the international community, only legitimizes and habituates law-breaking, further undermining international law's moral credibility. Interpretations of international law can be constructed that would narrow the gap between the legal rules and moral intuitions regarding the use of defensive force. Such revisionist interpretations may be a useful temporary measure, but are not a solution, because the gap between law and justice can be narrowed but not closed by reinterpretation alone. Ultimately, reform is required of international law's foundational texts. International law limitations on responses to aggression are also improper for reasons beyond their conflict with principles of justice instantiated in domestic criminal law. International law and domestic criminal law are importantly different. Most fundamentally, international law lacks an effective law enforcement system. In order to effectively control unlawful aggression, international law needs to have fewer limitations on responses to aggression than criminal law, not more limitations. A series of examples of such improper limitations are discussed. Each has the unfortunate effect of promoting aggression and instability by undermining effective deterrence. Again, there exist possible reinterpretations of international law that could avoid some of the improper limitations but, ultimately, a reform of international law's foundational texts is required. One important opportunity for reforming international law is currently being squandered. The Assembly of State Parties to the International Criminal Court has recently approved a resolution defining the international crime of aggression. However, rather than confront international law's existing problems, the drafters compounded them by imposing individual criminal liability on leaders of victim states who authorize defensive force in violation of flawed current law. Fortunately, the resolution will not go into effect until 2017 at the earliest. There is still time to change course